2006
DOI: 10.1007/s00198-006-0186-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound variables of the heel in Finnish men aged 18–20 yr: predictors, relationship to bone mineral content, and changes during military service

Abstract: Exercise is the most important determinant of ultrasonographic variables in men, aged 18-20 years. Physical loading during military training increases SOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
2
8
1
1
Order By: Relevance
“…Both QUS measures showed the best correlation with THBMD and the worst with WTBMD and PFBMD, findings in keeping with those of others [57,58,60]. Whilst consistent across studies, such findings run contrary to expectation given that these areas consist mainly of cancellous bone (similar to the calcaneus).…”
Section: Discussioncontrasting
confidence: 56%
“…Both QUS measures showed the best correlation with THBMD and the worst with WTBMD and PFBMD, findings in keeping with those of others [57,58,60]. Whilst consistent across studies, such findings run contrary to expectation given that these areas consist mainly of cancellous bone (similar to the calcaneus).…”
Section: Discussioncontrasting
confidence: 56%
“…A study on resistance training of the upper body performed three times a week for 4 months by males aged 18–25 years reported that SOS increased by 2% in the humerus10 ) . In a study of walking and running undertaken by 246 males aged 18–20 years, SOS increased by 1.3%; the study also reported a significant correlation between SOS and BMD28 ) . A study of 67 soccer players aged in their 20s who undertook high-strength soccer training, including high-impact training, over 5 years showed that SOS was higher for the soccer players that for people who did not exercise regularly29 ) .…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of bone fractures in young people has increased by 2.5 times compared with 10 years ago7 ) . To increase peak bone mass and prevent weakening bones at a young age, young people can undertake jump exercises, resistance training, and aerobic exercises10, 27,28,29,30,31 ) . However, a potential risk of this training is of bone fractures during the exercise programs due to high strength and applying a load to a limited part.…”
Section: Introductionmentioning
confidence: 99%
“…Basic military training has served as an opportune model to observe the effect of brief, high intensity, multi-mode, physical training interventions. After 14 weeks of basic training, male army recruits have been observed to improve calcaneal strength 179 , and increase leg bone mass by around 12%; those with the lowest initial values gaining the greatest amount 106,180 . Recruits who temporarily stopped training due to stress fracture also gained bone mass, but to a lesser degree (5%).…”
Section: Exercise Interventions In Young Adult Menmentioning
confidence: 99%